2023
DOI: 10.3389/fevo.2023.1203725
|View full text |Cite
|
Sign up to set email alerts
|

Responses of ecosystem water use efficiency to drought in the Lancang–Mekong River Basin

Abstract: The ecosystem water use efficiency (WUE), a crucial indicator of how climate change will affect terrestrial ecosystems, depicts the coupling of the carbon gain and water loss in terrestrial ecosystems. In this study, the spatiotemporal variations in the WUE and its responses to drought in the Lancang–Mekong River Basin (LMRB) from 1982 to 2018 were investigated using the gross primary productivity (GPP) and evapotranspiration (ET) data acquired from the Global Land Surface Satellite (GLASS) products. The analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…The findings revealed that meteorological drought events occurred frequently in the basin in recent years, particularly during the periods of 2004-2005, 2009-2010, 2012-2013, and 2015-2016, with long durations and severe drought conditions. These results are consistent with the historical natural disaster records of the LMRB in the international disaster database (https://public.emdat.be/data/ accessed on 1 October 2023) and with the results of previous studies [27,29]. In addition, by comparing the frequency and spatial distribution characteristics of meteorological drought events in the rainy season and dry season, and interannually in the LMRB, it was observed that even during the rainy season, meteorological drought events still occurred in the basin.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings revealed that meteorological drought events occurred frequently in the basin in recent years, particularly during the periods of 2004-2005, 2009-2010, 2012-2013, and 2015-2016, with long durations and severe drought conditions. These results are consistent with the historical natural disaster records of the LMRB in the international disaster database (https://public.emdat.be/data/ accessed on 1 October 2023) and with the results of previous studies [27,29]. In addition, by comparing the frequency and spatial distribution characteristics of meteorological drought events in the rainy season and dry season, and interannually in the LMRB, it was observed that even during the rainy season, meteorological drought events still occurred in the basin.…”
Section: Discussionsupporting
confidence: 92%
“…However, in recent years, the LMRB has been experiencing a worrisome escalation in both the frequency and severity of drought events, primarily attributed to the pervasive influence of global climate change. This distressing trend has resulted in far-reaching consequences for various sectors, including domestic water consumption, agricultural irrigation, ecological balance, and navigational activities across the countries encompassing the basin [28,29]. Thus, this study aimed to analyze the meteorological drought characteristics in the LMRB and identify the impact and correlation of atmospheric circulations on the meteorological drought in the basin.…”
Section: Introductionmentioning
confidence: 99%
“…But the use of remote sensing data, especially that from the same sensor inevitably introduces some potential uncertainties such as data self-correlated problem. Besides MODIS data, more and more remote sensing data products were used in WUE calculated such as GLASS data (Luo et al, 2023), Sentinel-2 data (Elfarkh et al, 2023) and PML-V2 product (He S. Y. et al, 2022;Ji et al, 2023). Different data sources may result in differences in evaluation results due to differences in resolution and model.…”
Section: Data Accuracymentioning
confidence: 99%